Pengaruh Kepuasan Kerja dan Komitmen Organisasi Terhadap Keinginan Berpindah Karyawan PT. Delami Garmen Kota Bandung - Wandy Zulkarnaen; Yayan Sofyan (Widya Cipta - Jurnal Sekretari dan Manajemen, 2018)
The purpose of this research is to find out how much influence job satisfaction and organizational commitment to desire to move simultaneously and partially at PT. Garment. The author uses research methods based on descriptive and verification analysis. "Descriptive research is research conducted to determine the value of an independent variable, either one or more (independent) without making comparisons, or linking with other variables."In this study the authors used path analysis with the analysis unit of employees of PT.Delami Garment while the samples arrived at the author of 143 people from the questionnaire distributed. Simultaneously Job Satisfaction and Organizational Commitment to PT Moving Desires.Delami Garment. Affecting the desire to move by 0.25 or 25% while the value of 0.75 or 75% is influenced by other factors not involved by this study such as compensation and work environment, while partially Job Satisfaction affects the desire to move by -45%, while Organizational Commitment affect the desire to move by -7, in general conditions of Job Satisfaction are being, Commitment of Medium Organizations and Desire of Moving Employees of PT.Delami Garment in high condition. There is a significant influence between Job Satisfaction and Organizational Commitment to the Desire of Moving Employees of PT.Delami Garments. Simultaneously, there is a negative and insignificant effect between Job Satisfaction on the Desire of Moving Employees of PT.Delami Garments. Partially, there is a negative and insignificant influence between Organizational Commitment to the Desire of Moving Employees of PT.Delami Garments. partially.